Analisis Sistem Pemungutan Pajak Kendaraan Bermotor (PKB) Melalui Layanan Drive Thru Dan Efeknya Terhadap Kepatuhan Wajib Pajak - Ghalib Kareem; Harun Ibrar (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
There is demand for transportation services from other sectors (such as agriculture, industry, trade, mining, fisheries and others) causing the provision of transportation services (Adisasmita: 2011). This is like what happened in the Pandaan area, East Java. Due to the large number of factories producing goods needed by the community, especially bottled drinking water, the demand for transportation services is also increasing. So transportation capacity must be provided in balance with demand, in order to be able to serve the development of activities in other sectors.